2014
DOI: 10.3109/19401736.2014.908354
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b gene reveals panmixia among Japanese Threadfin Bream, Nemipterus japonicus (Bloch, 1791) populations along the coasts of Peninsular Malaysia and provides evidence of a cryptic species

Abstract: We evaluated genetic differentiation among ten presumed Japanese threadfin bream, Nemipterus japonicus populations along the coast of Peninsular Malaysia based on the partial sequence of the mitochondrial cytochrome b gene (982 bp). Genetic divergences (Kimura-2 parameter) ranged from 0.5% to 0.8% among nine of the ten populations while these nine populations were 4.4% to 4.6% diverged from the Kuala Besar population located at the Northeast coast. The constructed Neighbour Joining (NJ) phylogenetic trees base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The parallel findings with Ning et al (2015) and Lim et al (2014) signifies the presence of a genetic barrier between the Indian Ocean and South China Sea for this demersal fish with the Straits of Malacca being the focal point of the two groups. Although on a smaller sizes, a detailed inspection showed that the same trend was also observed in N.…”
Section: Phylogenetic Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…The parallel findings with Ning et al (2015) and Lim et al (2014) signifies the presence of a genetic barrier between the Indian Ocean and South China Sea for this demersal fish with the Straits of Malacca being the focal point of the two groups. Although on a smaller sizes, a detailed inspection showed that the same trend was also observed in N.…”
Section: Phylogenetic Analysissupporting
confidence: 52%
“…A similar divergence value of 2.7% had been previously reported (Ning et al 2015) in N. japonicus populations from the Indian Ocean and West Pacific Ocean which was attributed to presence of cryptic species. Lim et al (2014) reported that while the populations of N. japonicus in the Straits of Malacca were panmictic from the Perlis waters in the Northwest to Kuala Sedili in the Southeast, a distinct cluster clade was observed in the South China Sea population of Tok Bali. In the current study clustering of N. japonicus in the NJ tree into two separate clusters clades separating the South China Sea, Sulu Sea and Celebes Sea from Indian Ocean (populations from Pakistan) suggests limited sharing gene pool between the two regions.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Lim et al . () analysed samples from both coasts of Malaysian Peninsular based on sequences from mitochondrial gene cytochrome b and found that this species might contain a regional cryptic species or distinct population in Kuala Besar in eastern Peninsular Malaysia. Likewise, three other molecular studies also pointed out the nature of cryptic diversity or local populations in India and Hainan Island (Menezes et al .…”
Section: Discussionmentioning
confidence: 99%
“…For the most studied species, N. japonicus, Ning et al (2015), using morphological and molecular methods, found two distinct cryptic species within this previous recognized single species, distributed in the Indian Ocean and West Pacific, respectively. Lim et al (2014) analysed samples from both coasts of Malaysian Peninsular based on sequences from mitochondrial gene cytochrome b and found that this species might contain a regional cryptic species or distinct population in Kuala Besar in eastern Peninsular Malaysia. Likewise, three other molecular studies also pointed out the nature of cryptic diversity or local populations in India and Hainan Island (Menezes et al 2002;Dong et al 2012;Ravitchandirane et al 2012).…”
Section: Exploration Of Species Diversity In the Nemipteridaementioning
confidence: 99%
“…In this study, two mitochondrial genes, 16S rDNA (16S) and cytochrome b (Cytb), that have been extensively employed in previous population genetic studies of marine organisms were used (Baharum & Nurdalila, ; Chiu, Bor, Tan, Lin, & Jean, ; Fernández‐Pérez et al, ; Lim, Ahmad, Nuruddin, & Mohd‐Nor, ; Maggi & González‐Wangüemert, ; Martínez et al, ; Shen et al, ). The use of different regions of DNA, which might be differently affected by evolutionary forces, provides a more complete picture of the current and past processes that influence the patterns of genetic variation and offers valuable data for the management of species.…”
Section: Introductionmentioning
confidence: 99%